69.8k views
4 votes
Solve the summation from n equals 2 to 9 of negative 3 plus 5 times n.

User Tyrondis
by
4.4k points

1 Answer

3 votes

Answer:


\sum^(n=9)_(n=2) (-3+5n)=196

Explanation:

Given : Expression the summation from n equals 2 to 9 of negative 3 plus 5 times n.

To find : Solve the expression ?

Solution :

The summation from n equals 2 to 9 of negative 3 plus 5 times n is written as,


y=\sum^(n=9)_(n=2) (-3+5n)

Solve,


y=(-3+5(2))+(-3+5(3))+(-3+5(4))+(-3+5(5))+(-3+5(6))+(-3+5(7))+(-3+5(8))+(-3+5(9))


y=(-3+5(2))+(-3+5(3))+(-3+5(4))+(-3+5(5))+(-3+5(6))+(-3+5(7))+(-3+5(8))+(-3+5(9))


y=(-3+10)+(-3+15)+(-3+20)+(-3+25)+(-3+30)+(-3+35)+(-3+40)+(-3+45)


y=7+12+17+22+27+32+37+42


y=196

Therefore,
\sum^(n=9)_(n=2) (-3+5n)=196

User Ivan Kuckir
by
5.4k points